High-resolution mapping of open chromatin in the rice genome - Zhang, Wenli; Wu, Yufeng; Schnable, James C.; Zeng, Zixian; Freeling, Michael; Crawford, Gregory E.; Jiang, Jiming (Genome Research, 2011)
Gene expression is controlled by the complex interaction of transcription factors binding to promoters and other regulatory DNA elements. One common characteristic of the genomic regions associated with regulatory proteins is a pronounced sensitivity to DNase I digestion. We generated genome-wide high-resolution maps of DNase I hypersensitive (DH) sites from both seedling and callus tissues of rice (Oryza sativa). Approximately 25% of the DH sites from both tissues were found in putative promoters, indicating that the vast majority of the gene regulatory elements in rice are not located in promoter regions. We found 58% more DH sites in the callus than in the seedling. For DH sites detected in both the seedling and callus, 31% displayed significantly different levels of DNase I sensitivity within the two tissues. Genes that are differentially expressed in the seedling and callus were frequently associated with DH sites in both tissues. The DNA sequences contained within the DH sites were hypomethylated, consistent with what is known about active gene regulatory elements. Interestingly, tissue-specific DH sites located in the promoters showed a higher level of DNA methylation than the average DNA methylation level of all the DH sites located in the promoters. A distinct elevation of H3K27me3 was associated with intergenic DH sites. These results suggest that epigenetic modifications play a role in the dynamic changes of the numbers and DNase I sensitivity of DH sites during development.
10.1101/gr.131342.111